Innovation Service Platform: Collaboration Based on Contest and Strategy Resources - Wang, Shu; Chen, Jin; Xie, Fang (Proceedings of Portland International Conference on Management of Engineering and Technology, 2011)
With providing a practical view of the current position of intellectual property (IP) the article notes the differing problems that need addressing in research and development (R&D) and technology transfer in China. For analyzing how to bridge public and private, science and business this study present several cases that incorporates the main mechanisms and processes necessary for stimulating innovation and creation of technology. Specifically the paper points to the increasing value of R&D crowdsourcing based on innovation contest through accessible innovation platform service. For how these services achieve the performance this study present such a tool in the form of a function model that helps to understanding what types of innovations can potentially choose and which innovative activities and collaboration are most clearly associated with improved performance systematically and strategically. Then we close by suggesting applications to technology transfer and IP services for future innovation in developing countries.<br
Keywords: Technological innovation; Collaboration; Integrated circuit; Patents; Awards activities; IP networks; industrial property; innovation management; technology transfer; innovation service platform; strategy resources; intellectual property; research and development; R&D; technology transfer; China; technology creation; crowdsourcing; IP services